Students’ Mathematical Connections in Circle Sector Learning Using the PMRI Approach with Bolu Kojo Context - Putri Aulia Ramasanti; Ratu Ilma Indra Putri (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2026)
This study aimed to describe students’ mathematical connection abilities in learning circle sectors through the Indonesian Realistic Mathematics Education (PMRI) approach using bolu kojo, a traditional Palembang cake, as a culturally relevant context. The study employed a descriptive mixed-method design involving 41 twelfth-grade students at SMA Negeri 10 Palembang. Quantitative data were obtained from a mathematical connection ability test, while qualitative data were collected through observations, written-response analysis, and semi-structured interviews. The research was conducted through preliminary, field-test, and teaching-experiment stages. During instruction, a PMRI-based student worksheet guided students in exploring the bolu kojo context, developing informal and formal mathematical models, participating in discussions, and progressively mathematizing contextual situations. After the learning session, students completed a test using a different context, namely a birthday cake, to examine their ability to transfer mathematical ideas beyond the instructional context. Mathematical connection ability was analyzed through four indicators: connecting concepts within the same mathematical topic, connecting concepts across different mathematical topics, applying mathematics to other disciplines, and relating mathematics to everyday life. The findings showed that students’ mathematical connection ability was generally in the medium category. The highest achievement occurred in connecting concepts within the same topic and relating mathematics to everyday life, with 95.1% of students meeting each indicator. Connections across mathematical topics were demonstrated by 65.9% of students, while 75.6% successfully connected mathematics with other disciplines. Interview findings revealed that high-, medium-, and low-ability students differed in contextual interpretation, proportional reasoning, use of scientific units, calculation accuracy, and completeness of mathematical representations. These results indicate that PMRI learning using the culturally familiar bolu kojo context can facilitate meaningful mathematical connections, although students still require support in writing systematic solutions, interpreting contexts accurately, and consistently using mathematical and scientific units.